Peran Kontrol Diri sebagai Mediator Hubungan Komunikasi Efektif Orang Tua Remaja dengan Agresivitas Remaja - Pratidina, Putu Ayu Onik; Marheni, Adijanti; Sampe Tondok, Marselius (Universitas Islam Indonesia, 2022)
Aggressiveness is one of the most critical problems in adolescents in their relationships with other people. Various factors that influence adolescent aggressiveness include effective parent- adolescent communication and self-control. However, there is still limited research examining the effect of effective parent-adolescent communication on adolescent aggressive behavior, especially mediated by self-control. This study aimed to determine the effect of effective parent-adolescent communication on adolescent aggressiveness mediated by self-control. The participants of this study were 228 high school students, middle adolescence (15-18 years). Data were collected using the Parent-Adolescent Effective Communication Scale, Aggressiveness Scale, and Self-Control Scale. The hypotheses were tested using mediation analysis using the JASP statistical program. The results showed that self-control partially mediated the relationship between effective parent-adolescent communication on adolesent aggressiveness. Furthermore, parents’ communication with adolescent girls was more likely to be open than with boys. These results can be a reinforcement that effective parent-adolescent communication plays an important role in the development of a child from an early age because it supports the development of self-control and behavior of children.